Stomatocytosis in a Beagle and Australian Cattle Dog. (10th October 2021) - Castillo, Daniel; Williams, Tim L.
Abstract: Background: Canine stomatocytosis is a well‐recognized rare erythrocyte disorder characterized by nonsyndromic forms with selective erythroid involvement, syndromic forms with extra‐hematologic disease, and acquired forms. Objectives: We describe serial clinicopathologic changes in two dogs with stomatocytosis of breeds that are different from those previously reported. Methods: Blood samples were obtained from a 12‐year‐old female neutered Australian Cattle Dog and a 12‐year‐old male neutered Beagle for hematologic and biochemical analyses, including a morphologic examination of peripheral blood films. Serial clinicopathologic data were reviewed, including CBCs performed by the referring veterinary surgeons. Results: Serial CBC data in both cases reported a variable decrease in RBC numbers commonly associated with a normal hematocrit, macrocytosis, hypochromasia, changes in red cell distribution width parameters including marked histogram abnormalities in volume distribution of the RBC population, and mildly increased or normal reticulocyte counts. Morphologic examination of peripheral blood films identified variable numbers of stomatocytes, knizocytes (Case 1, Day 1, Day 4), mild anisocytosis, mild macrocytosis, and mild polychromasia. Conclusions: In both cases, the changes exhibited in the erythrogram raise suspicion for an RBC membrane disorder with cell volume dysregulation and stomatocytosis, although they did not appear to cause clinically relevant hemolysis.